Contribuição para o estudo dos impactos do tratamento de dados pessoais na atividade empresarial sob a ótica da ANPD - Palmeira, Ellen Catarino (2023)
The sharing of data increasingly controls our lives and has a significant impact on society. To regulate and mitigate any violations of rights, national and international legislation has sought to protect the protection of personal data, through measures that bring transparency to the collection of data carried out by public and private organizations. In this sense, this research carried out an analysis of the legal aspects of data protection in Brazil, dedicating itself specifically to the role of companies in the search for data protection and the impacts of legislation on business activity from the perspective of the National Protection Authority of Data - ANPD To this end, a general overview of the evolution of the right to privacy will be addressed, rescuing the history on the subject, until the emergence of data protection and the enactment of the General Data Protection Law - LGPD, in Brazil. In addition, the necessary adaptations to be implemented by companies will be addressed, aiming at full compliance, as well as the hypotheses of sanctions applicable by ANPD, in case of data protection violations and their impacts on business activity. Thus, for the increment of the work, the hypothetical-deductive method was used, through the qualitative technique with documental, legislative and doctrinal analysis.